EVALUATION OF STUNTING CONTROL POLICIES IN KERKAP DISTRICT, NORTH BENGKULU REGENCY - Margaretha Rosaliana Situmeang; Bobby Mandala Putra; Heru Purnawan (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
The source of the problem is limited access to health services. The absence of adequate health services, especially in rural areas, can make it difficult to discover and treat malnutrition problems in children early. Children who suffer from Stunting are not only shorter than their peers but are also more susceptible to disease with the type of research applied being descriptive research with a qualitative approach. The aim is to find out the results of the Stunting Prevention Policy in North Bengkulu, especially the Stunting Family Assistance program. The research aspects that will be studied by researchers are: 1) the composition and ideal criteria are by the criteria in the family assistance program guidelines, 2) the work mechanism has been carried out by the family assistance program guidelines, people who are at risk of stunting receive referral services and social assistance from local government. 3) The work steps seen from the family support team work steps are good, they carry out monthly counseling at the posyandu once a month. 4) the division of tasks has been carried out well according to each section.